ANALISIS PENGARUH KESADARAN MEREK DAN PERSEPSI KUALITAS TERHADAP EKUITAS MEREK MELALUI LOYALITAS MEREK (Studi Kasus Pada Konsumen Minuman Marimas Di Kota Semarang) - Pamungkas, Bramaseto Rosie; Sugiarto, Sugiarto (Diponegoro Journal of Management, 2015)
This study was conducted on consumers drink fruit Marimas pollen in the city of Semarang. Top Brand Index shows that a decline in market share in the year 2012-2014. This study aims to provide empirical evidence whether Brand Awareness and Perceived Quality influence on Brand Loyalty and Brand Equity on the impact on consumers drink Marimas in Semarang.Â Samples were Marimas beverage consumers in the city of Semarang, amounting to 100 people. Data analysis method used is quantitative analysis using multiple linear regression analysis.Quantitive methods include the validity and reliability, the classic assumption test, testing hypothesis through F test, t test and the coefficient of determination (R2). And in this study using Sobel test to detect Brand Loyalty as intervening variable. The results showed that the Brand Awareness and Perceived Quality showed a positive influence on Brand Loyalty, Brand Loyalty subsequently accepted as an intervening variable in mediating the Brand Awareness and Perceived Quality to Brand Equity.